How not to run out of oxygen: Primary FRCA forcibly put into practice by COVID-19 to maintain patient safety. Issue 2 (April 2021) - Lake, Daniel; Henwood, Matthew; Eadie, Phil; Dagg, Kevin; Searle, Peter; Fenlon, Stephen; Iossifidis, Francoise
Background: SARS-CoV-2 is currently the cause of a global pandemic, putting significant strain on healthcare systems worldwide. Reports reaching the United Kingdom, ahead of the pandemic, and previous surge planning (H1N1 influenza) highlighted that pipeline oxygen supply could be strained. Therefore, this study was created to investigate the robustness of pipeline oxygen supply at Darent Valley Hospital. Coinciding news reports of hospitals declaring major incidents, due to oxygen failure, further backed the contingency planning. Methods: The maximum sustainable flow from the vacuum insulated evaporator (VIE) was calculated, followed by a snapshot survey identifying the exact usage of oxygen (litres per minute) across the entire hospital, also highlighting areas of high demand. A flowchart protocol was created for clinicians and engineers to follow should pipeline pressure drop. Finally, a second audit, monitoring oxygen usage and pipeline pressure, throughout the surge period, was undertaken. Results: The initial survey found a usage of 412.15 L/min, which increased to 1789 L/min during the surge, with the lowest pressure recorded at 3.6 bar. The output from the VIE plant was managed through cycling of its evaporators every 12 h, to prevent pipeline freezing. Conclusions: Data and contingency planning ensured maintenance of pipeline pressure throughout a pandemic surge of 576 COVID-19 patients. It also served as the foundation of a business case that resulted in, planning, approval, and installation of a second VIE plant in four weeks, ensuring readiness for further surge activity and future pandemics.